PERBEDAAN KARAKTERISTIK TEKANAN DARAH PASIEN STROKE HAEMORHAGIC DAN NON HAEMORHAGIC DI RSUD NABIRE TAHUN 2020 - Sukatemin Sukatemin (NHM PRESS, 2022)
Background: Every year there are 13.7 million new cases of stroke and about 5.5 million people die due to stroke. The purpose of the study: to determine differences in the characteristics of systolic blood pressure before and after stroke, differences in diastolic blood pressure before and after stroke, differences in systolic blood pressure per diastole before and after haemorhagic and non-haemorhagic stroke at Nabire Hospital in 2020.Research method: The research design used a cross sectional study, starting with the identification of patients in the Haemorhagic Stroke and Non Haemorhagic Stroke groups, the two groups looking for differences in the characteristics of each variable studied. Statistical test using Independent Sample T-Test. Sampling by accidental sampling with the number of samples in the haemoragic group was 36 and the non-haemoragic group was 30. Results : The difference in the characteristics of systolic blood pressure before a stroke was obtained with a P value of 0.000. In the variable difference in the characteristics of diastolic blood pressure before stroke, the value of P = 0.157, the variable difference in the characteristics of systolic blood pressure after a stroke, the value of P = 0.000, on the variable difference in the characteristics of diastolic blood pressure after stroke, the value of P = 0.000, on the variable Difference in pressure characteristics Systolic blood pressure per diastole before stroke obtained P value = 0.038 and the variable difference in characteristics of systolic blood pressure per diastole after stroke obtained P value = 0.002. Conclusion: There are differences in the characteristics of systolic blood pressure before and after stroke, diastolic blood pressure after stroke, systolic blood pressure per diastolic before and after a stroke and there is no difference in diastolic pressure before stroke in Haemorhagic and Non Haemorhagic Stroke patients at Nabire Regional General Hospital.